BUSINESS ORGANIZATION ANALYSIS IN THE FIELD OF IT CONSULTANT BUSINESS USING MCKINSEY 7S MODEL BASED ON CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) POINT OF VIEW AND COMPONENTS CHARACTERISTIC OF IT CONSULTANTS - Afifah Salihah; Sam'un Jaja Raharja; Herwan Abdul Muhyi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research aims to evaluate company performance, especially those in the IT consultant business. This research uses descriptive qualitative methodology to identify the company's performance by using McKinsey 7s Model. Interviews and observations with resource individuals were used as data collection approaches to acquire information on the process of achieving organizational or commercial goals. The main focus of this article is companies that provide IT consulting services. The author interviewed an informant from ABC Company engaged in the IT consulting business and an informant from XYZ Company involved in the same field. The study findings reveal that each company has its advantages and disadvantages. This piece has to improve good communication, an organized manager, and change agents. It is hoped that these findings may serve as a solution and motivation for these two businesses in resolving their issues.